Aleurotrachelus Quaintance & Baker (Hemiptera: Aleyrodidae) and allied genera from Taiwan - Dubey, Anil Kumar; Ko, Chiun-Cheng (Zootaxa, 2010)
Whitefly species from Taiwan of the genera Aleurotrachelus Quaintance & Baker, Cohicaleyrodes Bink-Moenen and Crenidorsum Russell are revised, based mainly on type specimens, together with keys to species, host-plant data, and puparial diagnoses of the genera. Five species are transferred from Aleurotrachelus: Cohicaleyrodes caerulescens (Singh) comb. nov., Co. rubi (Takahashi) comb. nov., Co. taiwanus (Takahashi) comb. nov., Crenidorsum alpinus (Takahashi) comb. nov., and Cr. elatostemae (Takahashi) comb. nov. Puparia are selected as lectotypes for each of the following species: A. fissistigmae Takahashi, A. pyracanthae Takahashi, Co. rubi, Cr. elatostemae, Cr. micheliae (Takahashi) and Cr. turpiniae (Takahashi). A neotype is designated for Co. taiwanus (Takahashi). Aleurotrachelus anonae Corbett and the genus Cohicaleyrodes Bink-Moenen are newly recorded from Taiwan. Drawings of the puparia, microscopic images and diagnosis of each species are given.